New environmental parameters to determine the amount of polluting chemical substance in effluents and emissions in Peruvian legislation - Zegarra Pumacayo, Jorge Luis (2022)
At present, the environmental legislation of our country regulates the "concentration of contaminating chemical substance", this is presented as a parameter expressed in the Maximum Permissible Limits (LMP). In Peru, it is considered that when the value of the "concentration of contaminating chemical substance" is exceeded, damage is caused to people's health and, in turn, a negative environmental impact is produced on the various ecosystems and biodiversity. The present investigation proposes to study, beyond the "concentration of contaminating chemical substance", to the "amount of contaminating chemical substance" understanding it as an object of evaluation and as a means to know to adapt a better control of environmental contamination that causes environmental damage. It is concluded that incorporating the new environmental parameters of: "flow of materials or flow rate (L / h)" and "process operation time (h)", working together with the parameter already used in environmental standards, that is, with the value of "concentration of chemical contaminant", the "mass quantity of chemical contaminant" can be quantified. Likewise, it is necessary to consider that these proposed parameters are, in practice, totally feasible to be measured.